A new species of Ernstia (Porifera: Calcarea) described from marine aquarium - Sanamyan, Karen; Sanamyan, Nadya; Martynov, Alexander; Korshunova, Tatiana (Zootaxa, 2019)
A new species of calcareous sponge, Ernstia pyrum sp. nov. (Calcarea, Calcinea, Clathrinida, Clathrinidae) is described from marine reef aquarium. It is assumed that its type locality is Indonesia. Molecular data render this species as a member of the genus Ernstia, although its morphology deviates in significant points from the original definition of the genus. In particular Ernstia pyrum sp. nov. has a clear atrial cavity not lined with choanocytes (true atrium), a feature not reported before for this genus.